Progressive facial hemiatrophy (Parry Romberg disease ). - Bonafé, J.L.; Delprat, A.; Arrué, Ph.; Boutault, F. (European Journal of Pediatric Dermatology, 2018)
Five cases of progressive facial hemiatrophy (Parry Romberg disease) are reported. Sex prevalence, etiophatogenic mechanisms, pathological findings of the different tissues involved and possible medical or surgical treatments are reported.